Risk Perception of Natural and Human-Made Disasters—Cross Sectional Study in Eight Countries in Europe and Beyond - Bodas, Moran; Peleg, Kobi; Stolero, Nathan; Adini, Bruria (Frontiers in Public Health, 2022)
Each year, emergency and disaster situations claim a heavy toll in human lives and economic loss. Civilian populations that are more aware and prepared for emergencies are more resilient. The aim of this study was to explore similarities and differences in risk perception of emergencies and disasters across different societies and its association with individual resilience. A cross sectional study that explored attitudinal factors, as expressed by diverse samples of target countries across Europe and beyond, took place during the months of January-February 2021. Diverse samples (N≥500) of adults from 8 countries (Italy, Romania, Spain, France, Sweden, Norway, Israel, and Japan) were engaged in this study. This study used the Pictorial Representation of Illness and Self-Measure (iPRISM) tool to assess risk perception. The results suggest that for the overall sample (N=4,013), pandemics were the risk of which participants showed the highest concern, followed by critical infrastructure fail, social disturbance, natural hazards, and extreme weather events. It was found that religiosity is associated with risk perception, with highly religious and non-religious reporting elevated risk perception (F=5.735, df=2, p=0.003), however country-specific analysis revealed that this finding varies depending on local contexts. The analysis also revealed differences in risk perception depending on age and type of risk. The results of this study present that there are commonalities and differences between societies across Europe and beyond concerning societal resilience at large, including risk perception. The dependency of risk perception on local context suggests that a regional-based approach for disaster risk reduction may be called for to adapt and adjust to local socio-cultural characteristics of each population.